High-performance ink-jet printed graphene resistors formed with environmentally-friendly surfactant-free inks for extreme thermal environments. (March 2017) - Michel, Monica; Biswas, Chandan; Kaul, Anupama B.
Graphical abstract: Highlights: The surfactant-free inks yield resistivity ρ values are 7× lower, i.e. 1.1 mΩ m, compared to 7.1 mΩ m for the surfactant-assisted formulations. Mechanical elasticity and robustness of the printed structures reveals minimal variations in resistance (∼8%) with bending radii of curvature up to 0.16 cm −1 . Thermal behavior of the printed features formed using the surfactant-free ink yields low temperature coefficient of resistivity, i.e. 1 Ω/K in the range of 6–80 K, or −2.7 × 10 −4  ppm/K. Abstract: In this work, a surfactant-free graphene ink is prepared in a mixture of terpineol ( T ) and cyclohexanone ( C ) and optimized to yield rheologies appropriate for ink-jet printing on both rigid SiO2 /Si and flexible polyimide substrates. The surfactant-free ink optimized here, clearly demonstrates its enhanced electrical transport characteristics, where resistivity ρ values are 7× lower, i.e. 1.1 mΩ m, compared to 7.1 mΩ m for the surfactant-assisted formulations derived from N-methyl-2-pyrrolidone (NMP) and ethyl cellulose (EC) reported earlier. The C:T surfactant-free ink is stable with aging, exhibiting minimal signs of graphene nano-membrane re-agglomeration. The mechanical elasticity and robustness of the printed structures is evaluated through strain-dependent bending tests that reveal minimal variations in resistance (∼8%) with bending radii of curvature up to 0.16 cm −1 . Finally, the thermal behavior of the printed features formed using the surfactant-free ink is deciphered from the Resistance–Temperature data obtained from 6 K to 350 K, where the temperature coefficient of resistivity (TCR) is calculated to be very low (e.g. 1 Ω/K in the range of 6–80 K, or −2.7 × 10 −4  ppm/K), comparable to other low TCR materials such as polymer/carbon composites. In summary, the resistive structures designed using the surfactant-free, environmentally-friendly inks formulated here, exhibit attributes that are extremely desirable for flexible electronics, such as enhanced electronic transport, good mechanical robustness and a TCR that varies minimally with temperature.